1997
DOI: 10.1046/j.1365-2893.1997.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus by retroviral vectors expressing antisense RNA

Abstract: Two retroviral vectors carrying an antisense gene from the hepatitis B virus (HBV) preS/S or preC/C were constructed and used to infect the human hepatoblastoma cell line 2.2.15, which expresses HBV surface antigen (HBsAg), HBV e antigen (HBeAg) and releases HBV particles. The results showed that the inhibitory effects of antisense gene transfer, mediated by retroviral vectors on the expression of HBV antigens, appeared as early as day 3 after transduction, reached a maximum on day 5 and persisted for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…MZPS1 inhibited viral production in 2.2.15 cells, and decreased viral production was observed after 72 hours of treatment with the minizyme. The observation is promising, as previous studies showed inhibition of viral production after prolonged treatments of 5-9 days with antisense ODNs (Korba and Gerin, 1995;Ji and Si, 1997). MZPS1 also inhibited HBsAg expression in 2.2.15 cells.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…MZPS1 inhibited viral production in 2.2.15 cells, and decreased viral production was observed after 72 hours of treatment with the minizyme. The observation is promising, as previous studies showed inhibition of viral production after prolonged treatments of 5-9 days with antisense ODNs (Korba and Gerin, 1995;Ji and Si, 1997). MZPS1 also inhibited HBsAg expression in 2.2.15 cells.…”
Section: Discussionmentioning
confidence: 54%
“…However there is still a need to systematically identify the most suitable conserved target sites on the HBV transcripts for minizyme action. Previous studies using PLC/PRF5 and 2.2.15 cells had shown that antisense ODNs targeted at the HBsAg ORF, the pre-S1 ORF, the core ORF, the encapsidation signal, and the polyadenylation signal can result in effective inhibition of HBsAg expression as well as viral replication (Goodarzi et al, 1990;Korba and Gerin, 1995;Ji and Si, 1997;Wu and Wu, 1992). These would serve as additional potential targets for op-timization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These core-specific antivirals may act at either the RNA level or the protein level. Efficient viral inhibition by targeting the core RNA, which is in fact the pgRNA, has already been demonstrated with RNA interference (Ying et al, 2003), antisense oligonucleotides (Ji & Si, 1997) and ribozymes (Feng et al, 2001). HBcAg has also been targeted at the protein level by aptamers (Butz et al, 2001), HeteroArylDihydropyrimidines or HAPs (Deres et al, 2003) and single-chain variable fragment (scFv) intrabodies (Yamamoto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both nucleic acid based and protein based antiviral strategies have been explored. Viral RNA has been successfully targeted by expression of antisense RNA [15,16,17,18] and ribozymes [19,20]. At the protein level the viral core protein has been extensively investigated as a potential target for resistance genes since it is the building block of viral nucleocapsids and plays an essential role in hepadnaviral replication [21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%